Tailoring the thermophysical properties of porous SiC framework reinforced Al-Mg-Si composites by Si alloying content for thermal energy management. (14th October 2020) - Zhang, Zhejian; Yuan, Yuan; Xie, Wenqi; Deng, Yuchen; Wei, Zhilei; Liu, Dangui; Shi, Zhongqi
ABSTRACT: SiC/Al composite is a promising thermal energy management material. However, promoting the thermal conductivity (TC) and decreasing the coefficient of thermal expansion (CTE) of SiC/Al composite simultaneously is a big challenge. Herein, three-dimensional (3D) porous SiC ceramic framework reinforced Al-Mg-Si alloy composites were prepared by spontaneous infiltration. The effects of Si alloying content on the phase composition, microstructure and themophysical properties of the composites were investigated. The results indicate that the increase of Si alloying content can not only inhibit the formation of Al4 C3 effectively, but also increase the concentrations and particle sizes of second phases including Mg2 Si and Si in infiltrated Al alloy. Consequently, the themophysical properties of the composites can be tailored by the Si alloying content. The composite with Si alloying content of 12 wt.% exhibits the superior themophysical properties with TC of 176.3 W∙m −1 ∙K −1 and CTE of 9.12 × 10 −6  K −1 .